Managing the Energy Transition. (May 2016) - Walters, Jonathan
This article explores how Central Asia can achieve the aspirations of Vision 2050 in the energy sector. Under this vision, the region's energy resources will have been developed in an efficient and sustainable manner by 2050. The complementarities between those energy resources will be effectively exploited by cross-border trade within the region and by substantial exports of clean energy to China, South Asia, Europe, and elsewhere. There will be an appropriate balance between renewable and nonrenewable energy, and hydrocarbons resources will have contributed to competitiveness and diversification of the economy, and will not have been wasted. This article reviews what the future may hold for energy technologies, since their development will critically affect the choices for Central Asia's energy transition. The article then considers the legacy of Soviet energy policy and what, in broad terms, Central Asia needs to do to achieve a successful energy transition. Subsequent sections consider specific aspects of the electricity, hydrocarbon, and renewable energy sectors. Possible options are then explored on how Central Asia might benefit from a global climate change deal in developing its renewables, while also addressing some of the troubling challenges of cooperation for developing the region's water resources for hydropower production and effective water storage.